How to Approach a Child About Concerns for Their Mental Health and Seeking Help: A Delphi Expert Consensus Study to Develop Guidelines on Mental Health First Aid for Supporting Children - Catherine L. Johnson; Claire M. Kelly; Anthony F. Jorm; William Garvey; Laura M. Hart (Health Expectations)
ABSTRACT Background Adults who live or work with children are an important source of support and are gateways to professional help when a child is experiencing a mental health problem. This study aimed to develop consensus‐based guidelines on how adults such as parents, educators or health professionals should approach a child aged 5–12 years to discuss concerns about the child's mental health and seek help. Methods A Delphi consensus method with three rounds was used. Experts were recruited from six countries to form three panels: health professionals, educators and people with lived experience (parents and carers, and young people with mental health problems). Statements to be rated were sourced from an online search of websites designed for adults who live or work with children. Further suggestions for statements came from panellists. Statements that reached 80% consensus across all panels were included in the guidelines. Results 132 participants completed the Round 1 survey, reducing to 54 by Round 3. A total of 248 statements were presented to panel members, with 151 being endorsed and included in the guidelines. Conclusions These guidelines represent the first recommendations developed for members of the public providing mental health first aid to children aged 5–12 years. Patient or Public Contribution Lived experience advocates (i.e. those with lived experience of a mental health problem in childhood and/or caregiving experience of raising a child with a mental health problem) were involved at two stages of this research: As part of the Advisory Group for the project and as expert panel members. Advisory Group members provided input into the conduct of the study and the content and design of the research outputs. Panel members provided their expertise to review every item to be included in the guidelines, proposed new items to be included, and reviewed and approved the finalised output documents.